Multi-scale exploration of multiphase physics in flows (MEMPHIS): A framework for the next-generation predictive tools for multiphase flows - Angeli,P; Azzopardi,BJ; Hewakandamby,B; Hewitt,GF; Pain,CC; Simmons,MJH; Matar,OK (2014)
In this paper, we outline the framework that we are developing as part of the Multi-scale Exploration of Multiphase PHysIcs in flowS (MEMPHIS) programme to create the next generation modelling tools for complex multiphase flows. These flows are of central importance to microfluidics, oil-and-gas, nuclear, and biomedical applications, and every processing and manufacturing technology. This framework involves the establishment of a transparent linkage between input and prediction to allow systematic error-source identification, and, optimal, modeldriven experimentation, to maximise prediction accuracy. The framework also involves massivelyparallelisable numerical methods, capable of running efficiently on 105-106 core supercomputers, with optimally-adaptive, three-dimensional resolution, and sophisticated multi-scale physical models. The overall aim of this framework is to provide unprecedented resolution of multi-scale, multiphase phenomena, thereby minimising the reliance on correlations and empiricism.